2020
DOI: 10.1109/access.2020.3013662
|View full text |Cite
|
Sign up to set email alerts
|

Resilience-Driven Modeling, Operation and Assessment for a Hybrid AC/DC Microgrid

Abstract: High-impact and low-probability extreme events can cause severe damage to power systems, especially for distribution systems. Microgrids (MGs) with distributed generation resources provide a viable solution for local load survivability via islanding schemes during extreme events. Recently, much research has focused on resilience-driven modeling and operations of MGs. In this paper, a resiliencedriven operational model incorporating two operational modes (grid-connected and islanded) and detailed technical char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…(3) Fragility model of DGs DGs are less affected by typhoon disasters and can provide power to support the MESs islanding operation [51,115,[117][118][119][120][121]. DGs' fragility model can be expressed by the failure probability of the normal operation of the system as follows: The indoor facilities of MECPSs, such as gas turbine, P2G, gas triple supply, energy storage, and other physical system equipment and cyber system equipment (protection and measurement) are indoor, which are less affected by the typhoon.…”
Section: ) Fragility Model Of Underground Cables and Pipelinesmentioning
confidence: 99%
“…(3) Fragility model of DGs DGs are less affected by typhoon disasters and can provide power to support the MESs islanding operation [51,115,[117][118][119][120][121]. DGs' fragility model can be expressed by the failure probability of the normal operation of the system as follows: The indoor facilities of MECPSs, such as gas turbine, P2G, gas triple supply, energy storage, and other physical system equipment and cyber system equipment (protection and measurement) are indoor, which are less affected by the typhoon.…”
Section: ) Fragility Model Of Underground Cables and Pipelinesmentioning
confidence: 99%
“…Load restoration-based methods are another purpose of increasing resilience that has been used in [19]. MGs with DG are introduced as a viable solution in [20], [21] for local load survivability during contingencies due to their islanding schemes. In this regard, according to a hybrid AC/DC MG resilience enhancement, a resilience-driven approach is presented in emergency and normal operation mode.…”
Section: Nomenclaturementioning
confidence: 99%
“…A comprehensive review on various control strategies in hybrid AC/DC microgrid is reported [4] where an extensive review covering various aspects such as modeling, energy management, and stability analysis is presented. Similarly, a DC microgrid with both grid and islanded modes is studied in detail [5] by conducting case studies to validate the resilience-based efficacy of the proposed approach. e authors in [6] implemented a resiliencybased approach by incorporating a battery energy storage system (BESS) with the existing grid-connected microgrid to address the critical loads (CLs) during grid outage conditions to ensure stable operation of hybrid AC/DC microgrid.…”
Section: Introductionmentioning
confidence: 99%